Fuzzy adaptive fault-tolerant controller design based on Nussbaum for nonlinear quadrotor UAV system with input saturation. (19th July 2019) - Hu, Chaofang; Zhang, Zelong; Zhou, Xianpeng; Sun, Binghan; Wang, Na
In this paper, an effective fuzzy adaptive fault-tolerant control (FTC) strategy is proposed for the six-DOF under-actuated model of a quadrotor UAV with actuator partial loss fault of effectiveness and saturation, accompanying with uncertain parameters and external disturbances. The hyperbolic tangent function is used to approximate the input saturation characteristics, and then transformed into the affine form of control input. For the unknown control gain caused by fault and saturation, Nussbaum technology is introduced to effectively avoid controller singularity problem. A fuzzy logic system is proposed to approximate the totally lumped unknown items resulted from uncertain parameters and external disturbances, besides faults and saturation. In the backstepping design process, the improved sliding mode filter and sliding mode control are respectively introduced to design fault-tolerant controllers for position and attitude dynamics to avoid the 'differential explosion' phenomenon and establish asymptotic stability. Simulation results demonstrate the power of the designed controllers.